Effect of Nearly Isometric ACL Reconstruction on Graft-Tunnel Motion: A Quantitative Clinical Study. Issue 12 (24th December 2019) - Wan, Fang; Chen, Tianwu; Ge, Yunshen; Zhang, Peng; Chen, Shiyi
Background: In anterior cruciate ligament (ACL) reconstruction, minimizing the graft-tunnel motion (GTM) will promote graft-to-bone healing and avoid graft loosening or tearing as well as potential bone tunnel enlargement. A nearly isometric state of the graft can be achieved by placing the tunnel properly to theoretically gain better graft-to-bone healing. However, little clinical evidence is available to quantify the relation between GTM and tunnel position. Purpose: To find the proper zones for the femoral and tibial tunnel apertures that minimize the GTM, referred to as the "nearly isometric zone, " through use of intraoperative GTM measurement and 3-dimensional computed tomography (3D-CT). Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 100 patients were enrolled in this study. Nearly isometric ACL reconstruction was performed, and an intra-articular GTM measuring device was designed to measure and record the amplitude of GTM while the knee was flexed from 0° to 120°. Postoperatively, the patients underwent multislice CT, and the images were used to create 3D-CT models. After tibial aperture examination, 5 patients were excluded due to the divergence of tibial aperture, and therefore 95 patients remained in the study. Patients were divided into 2 groups according to whether the lateral intercondylar ridge was absent or present. The Bernard-Hertel grid coordinates ( h, t ) of the femoral tunnel were then quantified. Results: The maximal GTM (mGTM) was a mean ± SD of 1.06 ± 0.66 mm (range, 0.0-3.0 mm). The mGTM in patients with a lateral intercondylar ridge was significantly lower than that in patients without a lateral intercondylar ridge (0.81 ± 0.39 vs 1.59 ± 0.73 mm, respectively; P < .0001). The average h and t were 0.227 ± 0.079 and 0.429 ± 0.770, respectively. Notably, in 1 patient, the mGTM was 0 mm whereas the coordinates ( h, t ) of the femoral tunnel were 0.250 and 0.255. The overall GTM slowly increased before 90° but increased significantly after the knee was bent 105° ( P = .010). Correlation analysis showed that the t coordiinate had significant correlation with mGTM ( R = 0.581; P < .001). A gradient pattern was created to show the nearly isometric blue zone (mGTM <0.5 mm), which was found to overlap with the IDEAL (isometric, direct insertion, eccentric, anatomic, low tension-flexion pattern) position. Conclusion: A method of measuring intraoperative GTM and quantifying femoral tunnel position on postoperative 3D-CT was successfully developed. The presence of a lateral condylar ridge can significantly reduce mGTM. A nearly isometric zone was described that was consistent with the IDEAL concept.